1988
DOI: 10.1007/bf02471425
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and copper changes after gastrectomy in aged patients with gastric cancer

Abstract: Serum zinc and copper levels were evaluated in patients with gastric cancer who had undergone gastrectomy. These patients were divided into two age categories; namely, the aged group, comprising 39 patients over the age of 70 years, and the younger group, comprising 23 patients younger than 50 years. The data before and after surgery were compared between the two groups. Serum zinc levels in the aged group were significantly lower than those in the younger group, both before and after surgery. Serum copper lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In more detail, H. pylori are the main risk factor in 65-80% of gastric cancers, but in only 2% of such infections (You et al, 2000;Testerman et al, 2006;Vilchis et al, 2009;Janjetic et al, 2010;Zamani et al, 2011). That is to say, despite the worldwide distribution of H pylori infection in patients with gastric disease, only a few number of infected individuals develop gastric cancer, It is important to clarify other factors that may determine risk among those infected with H. pylori (Hisaki et al, 1988;Lin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In more detail, H. pylori are the main risk factor in 65-80% of gastric cancers, but in only 2% of such infections (You et al, 2000;Testerman et al, 2006;Vilchis et al, 2009;Janjetic et al, 2010;Zamani et al, 2011). That is to say, despite the worldwide distribution of H pylori infection in patients with gastric disease, only a few number of infected individuals develop gastric cancer, It is important to clarify other factors that may determine risk among those infected with H. pylori (Hisaki et al, 1988;Lin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Such effects are known to result in somatic mutations. Nutritional deficiency of zinc results in delay of wound healing, growth retardation, anorexia, hyposmia and various skin dystrophies [2] Copper (Cu) is closely related with hematopoesis and the metabolism of osseous and connective tissue [3]. Prolonged copper deficiency is associated with anemia, leukemia, and osteoporosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, serum copper level was elevated in GC patients and significantly correlated to the survival time (61). Serum Cu: Zn ratio was also elevated, especially in advanced GC (62). Some studies focused on copper/zinc-superoxide dismutase (Cu/Zn-SOD) and found that serum levels of Cu/Zn SOD were significantly up-regulated in GC and higher Cu/Zn SOD levels indicated an increased risk of GC (63).…”
Section: Discussionmentioning
confidence: 99%